Evaluar índices productivos en pollos alimentados con 5, 10 y 15 % lenteja de agua (lemna minors) fresca, reemplazando balanceado - Bustamante Pizarro, Betty Yulissa (Machala : Universidad Técnica de Machala, 2018)
Poultry production is considered one of the largest sources that provide food for consumers, therefore, producers seek new food sources which lower production costs, both in management systems and in food. To this end, new forms of food administration have been created, such as automatic feeders, where elements can be added to the balance to be consumed by the chicken, the same happens with the water supply being made automatically or manually. The search for new raw materials that provide a good nutritional quality in the production birds are varied. In our case, an aquatic plant, a macrophyte rich in crude protein (35%) which contributes to the animal, has been considered for the present study. good amounts of proteins, amino acids and other nutrients that will serve for the normal development of birds. Lemna minor, also known as duckweed, is an aquatic plant that grows in abundance in humid, temperate places, basing its replication in stagnant or circulating water, counting with pH around 4.5 to 7.5, adapting to temperatures 15-24 ° C. This raw material was collected in the fish station "La Tembladera", of the Technical University of Machala, located in the Canton Santa Rosa, the administration of Lemna minors in the chickens was in different quantities (5, 10 and 15%) in replacement of balanced feed whose consumption was calculated based on the broiler consumption tables in their different weeks of the bird's life. The Lemna minors was mixed together by the complementary percentage of balanced feed, this mixture was well accepted by the bird in 100%. The study included 160 1-day-old broiler chickens, which were immediately placed in a conditioned area, in order to provide a minimum temperature of 30 ° C and a maximum temperature of 32 ° C, during the first week of life, in this period the birds are acclimatized; from the second week we worked on the trial with 4 treatments called Treatment 1 (Lemna minors at 5%), Treatment 2 (Lemna minors at 10%), Treatment 3 (Lemna minors at 15%) and finally, the control , that had only the administration of commercial balanced feed and each treatment had 4 homogeneous repetitions. The present investigation was carried out in the poultry facilities of Granja Santa Inés, corresponding to the Academic Unit of Agricultural Sciences of the Technical University of Machala. The variables to be studied are: weight gain, food consumption, feed conversion (carcass yield), mortality rates; in addition to assessing the cost of production, each result being determined separately in relation to the different values or results obtained by treatment, attributing said activity to the raw material under study, Lemna minor in the organism of the chicken, modifying the measurable and observable characteristics, and analyzing the organoleptic indicators with the criteria obtained from 120 people who participated in the tasting in the facilities of the Academic Unit of Agricultural Sciences.
La producción avícola está considerada una de las mayores fuentes que proveen alimento para los consumidores, por lo tanto, los productores buscan nuevas fuentes alimenticias las cuales abaraten costos de producción, tanto en los sistemas de manejo como en la alimentación. Con este fin, se han creado nuevas formas de administración del alimento, como comederos automáticos en donde se puede añadir elementos al balanceado para ser consumido por parte del pollo, lo mismo sucede con el suministro de agua realizándose de forma automática o manual. La búsqueda de nuevas materias primas que otorguen una buena calidad nutricional en las aves de producción son variadas, en nuestro caso se ha considerado para realizar el presente estudio una planta acuática, una macrófita rica en proteína cruda (35%) la cual aporta al animal buenas cantidades de proteínas, aminoácidos y otros nutrientes que servirán para el desarrollo normal de las aves. Lemna minor, también conocida como lenteja de agua, es una planta acuática que crece en abundancia en lugares húmedos, templados, basando su replicación en agua estancada o circulante, contando con pH alrededor de 4,5 a 7,5, se adaptan a temperaturas de 15-24 °C. Esta materia prima fue recolectada en la estación piscícola “La Tembladera”, de la Universidad Técnica de Machala, ubicada en el Cantón Santa Rosa, la administración de Lemna minors en los pollos fue en diferentes cantidades (5, 10 y 15%) en reemplazo de alimento balanceado cuyo consumo se calculó basándose en las tablas de consumo de broiler en sus diferentes semanas de vida del ave. La Lemna minors fue mezclada conjuntamente por el porcentaje complementario de alimento balanceado, esta mezcla fue bien aceptada por parte del ave en un 100%. El estudio contó con 160 pollos broilers de 1 día de edad, los cuales fueron ubicados inmediatamente en una área condicionada, con el fin de proporcionar una temperatura mínima de 30°C y máxima de 32°C, durante la primera semana de vida, en este periodo se aclimatan las aves; a partir de la segunda semana se trabajó en el ensayo con 4 tratamientos denominados Tratamiento 1 (Lemna minors al 5%), Tratamiento 2 (Lemna minors al 10%), Tratamiento 3 (Lemna minors al 15%) y por último, el testigo, que contaba solo con la administración de alimento balanceado comercial y cada tratamiento tuvo 4 repeticiones homogéneas. La presente investigación fue realizada en las instalaciones avícolas de la Granja Santa Inés, correspondientes a la Unidad Académica de Ciencias Agropecuarias de la Universidad Técnica de Machala. Las variables a estudiar son: ganancia de peso, consumo alimenticio, conversión alimenticia (rendimiento de carcaza), índices de mortalidad; además de valorar el costo de producción determinándose cada resultado por separado en relación a los diferentes valores o resultados obtenidos por tratamiento, atribuyendo dicha actividad a la materia prima en estudio, Lemna minor en el organismo del pollo modificando las características medibles y observables, además analizar los indicadores organolépticos con los criterios obtenidos de 120 personas que participaron en la cata en las instalaciones de la Unidad Académica de Ciencias Agropecuarias.
Keywords: CONVERSIÓN; CONSUMO; ALIMENTO; ORGANOLÉPTICOS